The Concept of Modern Law Polish and Central European Tradition - Jaron, Anna; Jaron, Anna (Peter Lang, 2019)
This book contains texts prepared by representatives of various branches of law, philosophers and dogmatists who link a general reflection on law with caselaw. This ensures that the presented approaches are versatile and insightful, and that the addressed issues vary, the most important of which is the oeuvre of the Polish jurisprudence and its contribution to building a modern state and legal theories. The context exceeds beyond a simple report on or presentation of this oeuvre and, in many cases, it only refers to it. The primary aim of this book is to determine, as follows: 1) the source (at least the potential source) of modernist solutions in the Polish law, 2) the realness of the modernist character of the said source and 3) the refection of these modernist solutions in the currently binding Polish law.